Strategi Penanganan Krisis Perusahaan di Era Digital: Studi Kasus Secbowl - Atika Shakila Salsabila; Nikmah Hadiati Salisah (Metacommunication: Journal of Communication Studies, 2025)
The rapid expansion of digital media has reshaped how companies handle crises, particularly when reputational risks intensify due to viral content on social platforms. This research explores the crisis management strategy of Secbowl, a food and beverage brand that encountered public criticism after viral social media posts questioned its service quality and operational reliability. Adopting a qualitative case study approach, the study relies on documentation analysis of online news reports and social media activity. The findings reveal that Secbowl initially implemented a rebuilding strategy as outlined in the Situational Crisis Communication Theory (SCCT), focusing on public apologies, transparency, and corrective initiatives. Social media became the primary channel for directly engaging stakeholders and regaining trust. However, as the crisis unfolded, new information emerged months later indicating that portions of the viral content were misleading or even fabricated. This shift underscores the necessity for organizations to employ crisis communication strategies that remain flexible and responsive to changing circumstances. In conclusion, while the rebuilding phase through apologies and remedial measures proved effective during the early stages, sustainable recovery required transitioning towards refuting misinformation and reaffirming credibility. These insights emphasize the pivotal role of digital platforms, not only in amplifying crises but also in influencing corporate responses and shaping stakeholder perceptions in today’s digital landscape.